FACTORS RELATED TO THE LEVEL OF GENERAL PATIENT SATISFACTION WITH INTERNAL MEDICINE CLINIC SERVICES IN DR. R. GOETENG TAROENADIBRATA THE REGIONAL PUBLIC HOSPITAL AREA OF PURBALINGGA 2019 - Septiono Bangun Sugiharto; Uji Yuni Hastuti; Taufik Heriyawan (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
ABSTRACT Background: According to the Law of the Republic of Indonesia Number 25 Year 2009 regarding Public Services, the state was obliged to serve every citizen of their human rights and meet their needs within the coverage of public services. One of many kinds of public service is health service. In Indonesia, health services should have definite standards, so it could improve the Indonesian people health status. To meet patients satisfactory is not an easy efforts, theres so many factors that affect patient satisfaction. Many of them is patient’s demographic such as age, sex, education level, and income. Method: This research uses quantitative methods. One kind of this research is to use analytic survey with Cross Sectional approach. The independent variable in this study is age (X1), sex (X2), education level (X3), and income (X4) and the dependent variable in this research is satisfaction level (Y). The sampling method in this study is non probability sampling with incidental sampling technique. Sampling from this research is 77 respondents. The research was held in months of September 2019. Data analysis was done by univariate, bivariate with chi square and contingency coefficients. Results: The results of this research showed that the difference of age is not related to satisfaction level (Asymp value. Sig = 0.657 α > α = 0.05), gender difference is not related to satisfaction level (Asymp value. Sig = 0.223 > α = 0.05 ), the difference in patient education level was related to satisfaction level (Asymp value. Sig = 0.000 < α = 0.05). Correlation between education level and satisfaction level is high (contingency coefficient value = 0.563) and income was related to satisfaction level (Asymp value. Sig = 0.001 < α = 0.05), correlation between education level and satisfaction level is moderate (contingency coefficient value = 0.505) Conclusion: Generally there is a high relation between the educational factor and the moderate relation with the income factor towards general patient satisfaction in the Regional Public Hospital dr. R. Goeteng Taroenadibrata Purbalingga internal medicine clinic services in 2019. Keywords: Age, gender, education level, income, satisfaction level. Library: 61 (2010-2018)